Derivados sintéticos de timol e carvacrol : efeitos na sobrevivência e comportamento de formigas cortadeiras e urbanas - Dantas, Jaciele de Oliveira (2023)
Environments transformed by humans provide resources and conditions necessary for the dispersion and colonization of red and leaf-cutting ants. The red ant of the genus Solenopsis is found in all terrestrial habitats; this insect is considered a significant agricultural, urban, and hospital pest. Likewise, the leaf-cutting ant of the genus Acromyrmex is considered a significant pest in agricultural and planted forest areas in the Neotropics. These ants are mainly managed using organosynthetic insecticides, although these insecticides are almost always toxic to non-target organisms and the environment. Furthermore, few active ingredients are registered for the control of these ants and the use of some is in the process of being suspended. In this scenario, plant essential oils rich in monoterpenes (e.g., thymol and carvacrol) are considered good alternatives to the use of conventional insecticides. The synthesis of new compounds from plant-derived molecules has proven to be successful in the management of important insect pests, showing that the variation of chemical radicals in the structure of the compound may be responsible for differences observed in its effects. Thus, analogous structures can assist in designing chemical substances with superior performance and they constitute a new advantage for discovery of safer insecticides. In this study, we evaluated the lethal and sublethal effects of thymol, of its synthetic derivatives, and of the insecticide deltamethrin on Acromyrmex balzani species and the acute toxicity, behavioral effects, and horizontal transfer effects of Lippia gracilis carvacrol oil and its derived compounds on Solenopsis sp. workers. In the first chapter, toxicity tests by topical application (LD and lethal time) and behavioral tests were carried out to assess changes in mobility and individual and group activities of Acromyrmex balzani workers. Thymol, its most toxic derivative (thymyl chloroacetate), and deltamethrin reduced the survival of workers and altered their individual and collective behavior. Such alterations can interfere with basic activities such as foraging, altering the integrity of the colony through several mechanisms. Thus, despite the desirable effects of deltamethrin on the control of ants, this insecticide is highly toxic and its use is in the process of being suspended. In the second chapter, bioassays of toxicity by topical application (DL and TL), of horizontal transfer, and of behavior were carried out to verify changes in individual and collective activities and in individual locomotion of Solenopsis sp. The essential oil of Lippia gracilis, carvacrol, and its synthetic derivatives showed insecticidal activity for the control of red fire ants. The treatments also interfered in locomotion behaviors. Carvacryl benzoate was the derivative that most reduced insect survival, possibly due to necrophoresis. These results show that carvacryl benzoate is promising in the development of new insecticides for the management of the genus Solenopsis sp.